Unitarizable and non-unitarizable represenations of algebras generated by idempotents - Popovych, S.; Turowska, L. (Algebra and Discrete Mathematics, 2004)
The problem of unitarization of representations
of algebras generated by idempotents with linear relations is studied. Construction of non-unitarizable representations for some subintervals of continuous spectrum is presented. Unitarization of representations from discrete series is proven.